Structure‐Based Design and Synthesis of Harmine Derivatives with Different Selectivity Profiles in Kinase versus Monoamine Oxidase Inhibition. (6th April 2017) - Bálint, Balázs; Wéber, Csaba; Cruzalegui, Francisco; Burbridge, Mike; Kotschy, Andras
Abstract: Dual‐specificity tyrosine‐phosphorylation‐regulated kinase 1A (DYRK1A) is an emerging biological target with implications in diverse therapeutic areas such as neurological disorders (Down syndrome, in particular), metabolism, and oncology. Harmine, a natural product that selectively inhibits DYRK1A amongst kinases, could serve as a tool compound to better understand the biological processes that arise from DYRK1A inhibition. On the other hand, harmine is also a potent inhibitor of monoamine oxidase A (MAO‐A). Using structure‐based design, we synthesized a collection of harmine analogues with tunable selectivity toward these two enzymes. Modifications at the 7‐position typically decreased affinity for DYRK1A, whereas substitution at the 9‐position had a similar effect on MAO‐A inhibition but DYRK1A inhibition was maintained. The resulting collection of compounds can help to understand the biological role of DYRK1A and also to assess the interference in the biological effect originating in MAO‐A inhibition. Abstract : Choosing sides : The different orientations of harmine in the X‐ray structures of this natural product bound to DYRK1A and monoamine oxidase A (MAO‐A) suggest chemical ways to fine‐tune the selectivity profile of this compound class. These structure‐guided transformations led to the abolition of DYRK1A and/or MAO‐A inhibition in harmine derivatives as well as to the synthesis of dual inhibitors of mixed inhibition ratio.